Verificação de programas C++ baseados no framework crossplataforma Qt - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
The software development for embedded systems is getting faster and faster, which generally incurs an increase in the associated complexity. As a consequence, consumer electronics companies usually invest a lot of resources in fast and automatic verification mechanisms, in order to create robust systems and reduce product recall rates. In addition, further development-time reduction and system robustness can be achieved through cross-platform frameworks, such as Qt, which favor the reliable port of software stacks to different devices. Based on that, the present work proposes a simplified version of the Qt framework, which is integrated into a checker based on satisfiability modulo theories (SMT), name as the efficient SMT-based bounded model checker (ESBMC++), for verifying actual Qt-based applications, and presents a success rate of 89%, for the developed benchmark suite. We also evaluate our simplified version of the Qt framework using other state-of-the-art verifiers for C++ programs and an evaluation about their level of compliance. It is worth mentioning that the proposed methodology is the first one to formally verify Qt-based applications, which has the potential to devise new directions for software verification of portable code.
Keywords: Framework Qt; Bounded Model Checking; Satisfiability Modulo Theories (SMT); ENGENHARIAS: ENGENHARIA ELÉTRICA